2012
DOI: 10.1155/2012/987402
|View full text |Cite
|
Sign up to set email alerts
|

Solid Rocket Motor Design Using Hybrid Optimization

Abstract: A particle swarm/pattern search hybrid optimizer was used to drive a solid rocket motor modeling code to an optimal solution. The solid motor code models tapered motor geometries using analytical burn back methods by slicing the grain into thin sections along the axial direction. Grains with circular perforated stars, wagon wheels, and dog bones can be considered and multiple tapered sections can be constructed. The hybrid approach to optimization is capable of exploring large areas of the solution space throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…[3] reinvigorated hybrid optimization techniques theory through a study in 2012 to enhance the efficiency of solid rocket motor design using hybrid optimization techniques. The researchers combined optimization algorithms including GA, PSO, and simulated annealing to optimize key parameters such as propellant composition, nozzle geometry, and chamber pressure [3]. The study revealed that the hybrid optimization approach outperformed individual optimization algorithms, producing optimal solid rocket motor designs.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…[3] reinvigorated hybrid optimization techniques theory through a study in 2012 to enhance the efficiency of solid rocket motor design using hybrid optimization techniques. The researchers combined optimization algorithms including GA, PSO, and simulated annealing to optimize key parameters such as propellant composition, nozzle geometry, and chamber pressure [3]. The study revealed that the hybrid optimization approach outperformed individual optimization algorithms, producing optimal solid rocket motor designs.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The optimal design with a more complicated area profile than a neutral profile is performed to confirm the usefulness of the proposed grain design method [34]. This study used regressive-progressive (RP) grain to confirm whether various classification models are helpful for complex grain design.…”
Section: Rp Grain Optimal Design Using Multiclass Svmmentioning
confidence: 99%
“…Various attempts have been made to combine global and local optimization algorithms in order to overcome the challenges of using them separately [10,[17][18][19][20][21]. Most of these studies used a combination of a global (e.g., GA) and a local optimization algorithm, which can be referred to as a hybrid optimization algorithm.…”
Section: Hybrid Optimization Algorithm For Thrust Allocationmentioning
confidence: 99%